Plasmacytoma skull: A rare entity - Fulare, S; Deshmukh, Satish; Nawkare, Ritesh; Sawarkar, Shriniket (Indian Journal of Case Reports, 2020)
Plasmacytoma is a localized accumulation of abnormal plasma cells that grow within the soft-tissue or bony skeleton. Solitary plasmacytoma most commonly occurs in the bones of the axial skeleton, such as vertebra, skull, and others. Extramedullary type of plasmacytoma is generally observed in the head and neck and most frequently observed in the nasal cavity and nasopharynx. We want to enlighten the case of a 55-year-old hypertensive female patient who presented with a swelling on the left side of the forehead of size 7 cm × 4 cm for 2 years, which was associated with a constant headache. Her computed tomography scan of the brain with a three-dimensional reconstruction of the skull was suggestive of a diffuse swelling involving the left side of the forehead suggestive of a calcified lesion involving the skull with no involvement of the brain parenchyma. The patient was then subjected to elective craniectomy and was planned for cranioplasty after 6 weeks. Histopathology was suggestive of lymphoproliferative disease/plasmablastic lymphoma, after which the patient was subjected to radiotherapy.